2012
DOI: 10.1111/j.1523-5378.2012.00983.x
|View full text |Cite
|
Sign up to set email alerts
|

Extragastric Manifestations of Helicobacter pylori Infection

Abstract: In the last year, different diseases possibly linked to Helicobacter pylori infection but localized outside of the stomach have been investigated. There are, in fact, several studies concerning cardiovascular diseases, hematologic disorders, neurologic diseases, metabolic, hepatobiliary diseases, and other conditions. Some of those studies, such as those on sideropenic anemia and idiopathic thrombocytopenic purpura, are quite large and well conducted, while in other cases there are just small or isolated studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(56 citation statements)
references
References 53 publications
1
42
0
13
Order By: Relevance
“…This is supported by several reports that indicate a correlation between H.pylori infection and various extra-gastric disorders (Banić et al, 2012), including some serious pregnancy-related pathologies, such as pre-eclampsia and/or fetal growth restriction (Cardaropoli et al, 2014). These pregnancy disorders, as well as numerous cases of miscarriage, mainly involve abnormal placentation.…”
Section: Introductionsupporting
confidence: 57%
“…This is supported by several reports that indicate a correlation between H.pylori infection and various extra-gastric disorders (Banić et al, 2012), including some serious pregnancy-related pathologies, such as pre-eclampsia and/or fetal growth restriction (Cardaropoli et al, 2014). These pregnancy disorders, as well as numerous cases of miscarriage, mainly involve abnormal placentation.…”
Section: Introductionsupporting
confidence: 57%
“…There are studies that indicated ophthalmic diseases (Sergio et al, 2006;Kountouras et al, 2011;Choi et al, 2010). A report by Banić et al (2012) is correlation between the iris color and certain conditions such as cataract and AMD with lighter eye colors. Several somatic or hereditary disorders can easily be recognized by the characteristic changes of the iris by just looking at it or the overlying cornea or intervening lens (Hashemi et al, 2010;Morrison, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…This response is attributed to molecular mimicry of infection-related bacterial proteins. The principal antigens associated with the autoimmune response against the platelets include the amino acid sequences of virulence factors such as VacA, CagA [17,178] and urease B, which are present during H. pylori infection [210]. The similarities shared between these antigens and platelet surface glycoproteins, like the glycoprotein IIIa among other platelet antigens not yet identified, are associated with antiCagA antibody production [178] and demonstrate the importance of H. pylori infection in ITP.…”
Section: Pathophysiology Of Secondary Itp (Associated With H Pylori mentioning
confidence: 99%
“…Since the discovery in 1983 that the stomach could be colonized by bacteria [3], sufficient evidence has accumulated implicating H. pylori as a pathogen intimately related to benign stomach diseases, such us chronic gastritis and duodenal and gastric peptic ulcers [3], and malignant diseases, for example gastric cancer [4] and gastric MALT lymphoma [5]. Furthermore, during the last three decades following the discovery [3], approximately 50 extragastric diseases have been reported in medical specialties such as cardiology, dermatology, endocrinology, obstetrics and gynecology, pneumology, neurology, odontology, ophthalmology, otorhinolaryngology, pediatrics, and hematology [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], the last of which is the subject of this review.…”
Section: Introductionmentioning
confidence: 99%